Case studies on the interaction between education and productive work - UNESCO (UNESCO)
This document consists of 11 case studies designed to throw light on the main theme of the 38th session of the International Conference on Education, namely, the integration of education and productive work. Guyana was among the countries reporting their experiences in this area
Reply to questionnaire ED/BIE/CONFINTED/38Q.1/80
Keywords: Education and employment